2014
DOI: 10.1038/srep05716
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistive performance and comparison of supermagnetic nanoparticles on giant magnetoresistive sensor-based detection system

Abstract: Giant magnetoresistive (GMR) biosensors have emerged as powerful tools for ultrasensitive, multiplexed, real-time electrical readout, and rapid biological/chemical detection while combining with magnetic particles. Finding appropriate magnetic nanoparticles (MNPs) and its influences on the detection signal is a vital aspect to the GMR bio-sensing technology. Here, we report a GMR sensor based detection system capable of stable and convenient connection, and real-time measurement. Five different types of MNPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 37 publications
(40 reference statements)
1
41
1
1
Order By: Relevance
“…GMR chips were manufactured with photolithography technique based on silicon wafer. GMR sensor and chip design was similar to that developed by Wang, et al [4]. Thirty-six (6×6 array) sensors are usable for one chip, and each sensor can work independently.…”
Section: Introductionmentioning
confidence: 99%
“…GMR chips were manufactured with photolithography technique based on silicon wafer. GMR sensor and chip design was similar to that developed by Wang, et al [4]. Thirty-six (6×6 array) sensors are usable for one chip, and each sensor can work independently.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sensors can be mass produced, making them low cost and disposable (Hall et al, 2010). Other groups have also shown that GMR sensors could be applicable to a myriad of biomedical applications (Baselt et al, 1998;Graham et al, 2004;Sandhu, 2007;Schotter et al, 2004;Wang et al, 2014). With the multitude of advantages, GMR sensor arrays provide food manufacturers and allergic patients or caretakers with an attractive solution to the need for highly sensitive and specific detection of any multiple trace allergen contaminants in food samples.…”
Section: Introductionmentioning
confidence: 99%
“…GMR sensor and chip design was similar to that developed by Wang, et al [4]. Sixteen (4×4 array) sensors are usable for one chip, and each sensor can work independently.…”
Section: Methodsmentioning
confidence: 99%